2000
DOI: 10.2169/internalmedicine.39.940
|View full text |Cite
|
Sign up to set email alerts
|

Acute Aortic Valvular Regurgitation Secondary to Avulsion of Aortic Valve Commissure in a Patient with Pseudoxanthoma Elasticum.

Abstract: A 68-year-old womandeveloped acute pulmonary edema due to severe acute aortic valvular regurgitation. At the time of emergency surgery, it turned out to result from spontaneous avulsion of the aortic valve commissure.Later, the patient was diagnosed to have pseudoxanthoma elasticum based on typical skin lesions. Connective tissue abnormalities associated with pseudoxanthoma elasticum might have contributed to the development of the avulsion of the aortic valve in this particular patient. (Internal Medicine 39:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…It should be noted that PXE associated with aortic regurgitation has been described previously in only one case report 6 and it was thus difficult to determine whether the aortic regurgitation of case 4 was due to PXE. However, even when we excluded this case from the CVD-positive group, the presence of CVD was still significantly associated with a high distribution score (P = 0.013) and the presence of mucosal lesions (P = 0.003).…”
Section: Case Reportsmentioning
confidence: 89%
See 1 more Smart Citation
“…It should be noted that PXE associated with aortic regurgitation has been described previously in only one case report 6 and it was thus difficult to determine whether the aortic regurgitation of case 4 was due to PXE. However, even when we excluded this case from the CVD-positive group, the presence of CVD was still significantly associated with a high distribution score (P = 0.013) and the presence of mucosal lesions (P = 0.003).…”
Section: Case Reportsmentioning
confidence: 89%
“…In 2006, Ringpfeil proposed simple criteria that excluded the autosomal dominant type of PXE, in which a patient is diagnosed as having minimally affected PXE when he or she exhibits pathological changes and angioid streaks. 6 According to these criteria, all of the PXE patients in this study can be diagnosed as having minimally affected PXE.…”
Section: Diagnosismentioning
confidence: 92%
“…In some cases, echocardiography demonstrated marked MVP of the both leaflets and vegetation‐like thickening of the anterior leaflet of the MV. Only 1 case was reported with right‐sided cardiac involvement in osteogenesis imperfecta 15–17…”
Section: Connective Tissue Diseasementioning
confidence: 99%
“…Rupture of fenestrated aortic cusps has also been implicated to cause acute, severe AI . Connective tissue abnormalities that weaken aortic cusp tissue have also been implicated in AV spontaneous rupture, such as was reported by Hirata et al in a patient with confirmed pseudoxanthoma elasticum …”
Section: Patient Profilementioning
confidence: 73%
“…Aortic valve (AV) rupture is a rare, but well described event . It occurs most commonly in the setting of blunt chest trauma but can also occur spontaneously in the setting of structurally or molecularly abnormal valves.…”
Section: Patient Profilementioning
confidence: 99%